Reducing Anxiety in HIV/AIDS Patients Through Cognitive Therapy - Suriyani Suriyani; Frengky Apay; Sofietje J. Gentindatu; Ellen R.V Purba (Science Midwifery, 2022)
This study aims to determine the effect of giving cognitive therapy in reducing anxiety in people with HIV/AIDS. The research subjects were 8 women with HIV/AIDS. Data collection was carried out using an anxiety scale, interviews and observations. The research design used was the Pretest-Posttest Control Group Design. The research analysis used is quantitative and qualitative analysis. Quantitative analysis by testing the hypothesis using the Mann-Whitney test analysis to determine whether there is an effect of cognitive therapy in reducing anxiety in HIV/AIDS sufferers in the study group before being given training and after being given training. Qualitative analysis was carried out based on the results of observations, interviews, worksheets. The results of the study, namely the pre-test and post-test anxiety showed that there were differences in anxiety after being given training with a value of Z = -2.309, p = 0.021, p <0.05. In the post-test and follow-up study groups there was a difference in anxiety with a value of Z = -2.323, p = 0.020, p <0.05. The conclusion of this study is that there are differences in the level of anxiety in the study subjects after follow-up.